2011
DOI: 10.1542/peds.2011-0218
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Prescribing During Pediatric Ambulatory Care Visits for Asthma

Abstract: OBJECTIVE: National guidelines do not recommend antibiotics as an asthma therapy. We sought to examine the frequency of inappropriate antibiotic prescribing during US ambulatory care pediatric asthma visits as well as the patient, provider, and systemic variables associated with such practice. PATIENTS AND METHODS: Data from the National Ambulatory Medical Care Surveys and National Hospital Ambulatory Medical Care Survey were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 45 publications
3
52
1
Order By: Relevance
“…Although one could argue that medical practices differ between private clinics and family practice teaching units, 30 we believe that the difference in outcomes observed at baseline can be attributed to a seasonal effect (baseline recruitment in late fall and winter in the pilot study v. summer and early fall in the current trial); this has been observed in other studies. 31 The seasonal effect might also explain the 13% increase in prescriptions in the control group between baseline (recruitment in the summer) and after the intervention (recruitment in the winter).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although one could argue that medical practices differ between private clinics and family practice teaching units, 30 we believe that the difference in outcomes observed at baseline can be attributed to a seasonal effect (baseline recruitment in late fall and winter in the pilot study v. summer and early fall in the current trial); this has been observed in other studies. 31 The seasonal effect might also explain the 13% increase in prescriptions in the control group between baseline (recruitment in the summer) and after the intervention (recruitment in the winter).…”
Section: Discussionmentioning
confidence: 99%
“…• 99 of 144 eligible physicians and 210 patients; median practice size = 40 physicians, range [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] Clusters analyzed n = 4 units…”
Section: Participantsmentioning
confidence: 99%
“…18 In 2011, nearly 1 in 6 pediatric ambulatory care visits for asthma ended with a prescription for an antibiotic without another ICD-9 code to justify its use, raising the concern for unnecessary antibiotic use. 19 With concern about antibiotic overutilization for asthma, along with previous reports of antibiotic use in asthmatic subjects of ∼20%, an ABC of 6.6% seems to be an appropriate goal. We also demonstrated an ABC of 24.5% for CXR use in asthma management, which is consistent with literature that supports the belief that CXR is not routinely indicated for asthma exacerbations but only in circumstances with clinical suspicion for alternate diagnosis (eg, pneumothorax, foreign body, pneumonia).…”
Section: Asthmamentioning
confidence: 99%
“…Patients were excluded from the analysis of antibiotic prescribing for OM if a diagnosis of another condition warranting antibiotics was made concomitantly (eg, mastoiditis, acute pharyngitis, acute tonsillitis, nonviral pneumonia, streptococcal sore throat or scarlet fever, acute sinusitis, peritonsillar abscess, urinary tract infection, or skin and soft tissue infection). 15 Narrowspectrum antibiotics consisted of penicillins (including amoxicillin), firstgeneration cephalosporins, tetracyclines, and sulfonamides. 16 Broad-spectrum antibiotics included macrolides (eg, azithromycin), quinolones, broad-spectrum penicillins (eg, b-lactam/b-lactamase inhibitor combinations), lincomycin derivatives (clindamycin), and broad-spectrum (second-or third-generation) cephalosporins.…”
Section: Antibiotic Prescribingmentioning
confidence: 99%